Comparative Deflection Hardening Behavior of Fly Ash-Based Geopolymer Composite with the Conventional Cement-Based Composite - Nematollahi, B.; Sanjayan, J.; Shaikh, Faiz (Nakhon Ratchasima Province 30000 Thailand, 2014)
This paper compares the behavior of a recently developed fly ash-based ductile fiber reinforced geopolymer composite (DFRGC) exhibiting deflection hardening and multiple cracking behavior in flexure with its cement-based counterpart commonly known as ductile fiber reinforced cementitious composite(DFRCC) composed of ordinary Portland cement (OPC) matrix. The geopolymer matrix of the DFRGC was composed of a low calcium (Class F) fly ash activated by 8.0 M NaOH solution (28.6% w/w) andNa2SiO3 solution (71.4% w/w) with a SiO2/Na2O ratio of 2.0. Randomly oriented short poly vinyl alcohol (PVA) fibers (2% v/v) were used to reinforce the brittle geopolymer and cement-based matrices. The matrix and composite properties of the geopolymer and cement-based composites including workability of the fresh matrix, density, compressive and flexural strengths, deflection capacity, composite ductility in flexure and composite toughness were evaluated. Experimental results revealed that the developed fly ash-based DFRGC exhibited superior deflection capacity, compressive and flexural strengths with significantly enhanced composite ductility and toughness compared to the con.This paper compares the behavior of a recently developed fly ash-based ductile fiber reinforced geopolymer composite (DFRGC) exhibiting deflection hardening and multiple cracking behavior in flexure with its cement-based counterpart commonly known as ductile fiber reinforced cementitious composite(DFRCC) composed of ordinary Portland cement (OPC) matrix. The geopolymer matrix of the DFRGC was composed of a low calcium (Class F) fly ash activated by 8.0 M NaOH solution (28.6% w/w) andNa2SiO3 solution (71.4% w/w) with a SiO2/Na2O ratio of 2.0. Randomly oriented short poly vinyl alcohol (PVA) fibers (2% v/v) were used to reinforce the brittle geopolymer and cement-based matrices. The matrix and composite properties of the geopolymer and cement-based composites including workability of the fresh matrix, density, compressive and flexural strengths, deflection capacity, composite ductility in flexure and composite toughness were evaluated. Experimental results revealed that the developed fly ash-based DFRGC exhibited superior deflection capacity, compressive and flexural strengths with significantly enhanced composite ductility and toughness compared to the conventional DFRCC.ventional DFRCC.